Comparing synchronous and asynchronous online discussions for students with disabilities: The impact of social presence - Dahlstrom-Hakki, Ibrahim; Alstad, Zachary; Banerjee, Manju (Computers and education, 2020)
The affordances of online learning have the potential to improve learning outcomes for students with disabilities by allowing customization and flexibility to meet individual needs. However, there are significant executive function and language processing demands that may be particularly challenging for this population. With that in mind, interventions guided by social presence theory may increase students' ability to engage in online settings. This study implemented a computer mediated, blended classroom setting in order to assess students’ understanding of statistics concepts following synchronous and asynchronous online, video-based discussion sessions. Social presence theory predicts that the immediacy of synchronous interactions should improve social presence, thereby increasing student engagement and performance. Data was collected from 105 students with high-incidence disabilities using a mixed methods experimental design with a within subjects quantitative component. Our findings indicate that while students with disabilities expressed preference for synchronous discussions, including self-reported greater engagement and self-reported improved comprehension, their performance on assessments of conceptual understanding was slightly better following asynchronous discussions. Implications for these disparities between preference and performance are discussed. •Social presence was manipulated by comparing synchronous and asynchronous discussions.•Students with disabilities expressed preference for synchronous discussions.•Greater comprehension was self-reported in the synchronous condition.•Performance on test of conceptual understanding was better in asynchronous condition.•Cognitive demands were higher in the synchronous condition.